Association of APOA5 rs2075291 and CIDEB rs2144492 polymorphisms with hypertriglyceridemia in individuals with traditional Chinese medicine dampness syndrome: a case-control study - Liu, Na; Zeng, Hongli; Cai, Xiangsheng; Yang, Shuo; Chen, Xinyan; Jiang, Guli; Yuan, Jiamin; Cai, Jianxiong; Zhou, Hui (Frontiers in Genetics, 2025)
PurposeTo investigate the association between polymorphisms of the APOA5 rs2075291 and CIDEB rs2144492 loci and hypertriglyceridemia (HTG) in a population with Traditional Chinese Medicine (TCM) dampness syndrome.MethodsA case-control study was conducted, enrolling 100 HTG patients and 100 age-matched controls with normal triglyceride levels from the physical examination cohort at Guangzhou 11th People’s Hospital (January–December 2023). Peripheral blood samples were collected to analyze APOA5 rs2075291 and CIDEB rs2144492 polymorphisms using PCR and sequencing. Lipid profiles were measured via an automated biochemical analyzer. Statistical analyses (chi-square tests, correlation analysis, and logistic regression) evaluated associations among gene polymorphisms, dampness syndrome, and HTG.ResultsThe observation group showed significant differences in genotype frequencies of APOA5 rs2075291 (OR = 2.916, 95% CI:1.160–7.334, χ2p = 0.019) and CIDEB rs2144492 (OR = 1.688, 95% CI:0.886–3.141, χ2p = 0.042) versus the control group. Significant intergroup differences were also observed in allele frequencies of APOA5 rs2075291 (OR = 2.727, 95% CI:1.113–6.682, χ2p = 0.023) and CIDEB rs2144492 (OR = 1.837, 95% CI:1.040–3.244, χ2p = 0.034). Stratified by dampness syndrome status, in the dampness syndrome subgroup, the HTG group had a higher frequency of CIDEB rs2144492 TG/TT genotypes than controls, though the difference was not significant (OR = 2.065, 95% CI:0.816–5.226, χ2p = 0.146). No significant difference in gene frequency was observed after FDR correction (p = 0.043, FDR threshold = 0.042). APOA5 rs2075291 showed no significant genotype/allele frequency differences (p > 0.05). In the non-dampness subgroup, FDR correction (p ≤ 0.033) revealed no significant differences in APOA5 rs2075291 genotype (OR = 4.083, 95% CI:0.977–17.063, χ2p = 0.041) or allele frequencies (p = 0.05), nor in CIDEB rs2144492 genotypes/allele frequencies (p > 0.05). Triglyceride levels did not differ significantly between dampness/non-dampness groups across genotypes (p > 0.05). Multivariate logistic regression identified male gender, higher BMI, dampness syndrome, and APOA5 rs2075291 genotype as independent risk factors for HTG (p < 0.05), while CIDEB rs2144492 trended toward significance (p = 0.05).ConclusionAPOA5 rs2075291 and CIDEB rs2144492 polymorphisms are associated with hypertriglyceridemia. Dampness syndrome individuals with CIDEB rs2144492 variants may have increased HTG predisposition. Larger cohort studies are warranted to validate these findings and explore underlying mechanisms.